Determination of the Load Center for Planetary Gears in Wind Turbine Gearboxes Based on Strain Testing - Zeng Jiyong; Yuan Baogang (Jixie chuandong)
The planetary bearing is one of the most important components for wind turbine gearboxes, due to the complication of the load and the special position. How to analyze the load center becomes the critical job for design engineers. Based on current design specifications, two 3 MW gearboxes with back to back arrangement are tested on the 10 MW testing benches, and strain testing is conducted on planetary gears during the experiment. For further utilization of these testing results about the strain of the gear, the least square method is taken to precisely estimate the load position of the applied center for the planetary bearings during the development for the new wind turbine gearbox.